PENDERITA DENGAN HEMOKROMATOSIS PRIMER - Kadek Mulyantari; A.A.Wiradewi Lestari; A.A.N. Subawa; Tjokorda Gede Oka; Sudewa Djelantik (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
Primary Hemochromatosis is a hereditary disease that occurs predominantly in man. Among men, clinical signs and symptomsfrequently appears on 40 years until more than 60 years of age. Meanwhile, the signs and symptoms among women appear on 50 yearsof age or after menopause. It is a very rare case in children or young adult. Secondary hemochromatosis can be differentiated fromprimary hemochromatosis based on existence of other underlying disease and secondary hemochromatosis often occurs in patient withmultiple blood transfusions. The diagnosis of primary hemochromatosis is confirmed by chromosomal test and liver biopsy to confirmthe liver damage caused by excessive iron accumulation. The main treatment of primary hemochromatosis is phlebotomy. The purposeof this method is to remove overload iron in body. In this case, the patient was man, unmarried, 51 years old, Australian. Four yearsago, he had complained about arthropathies, chronic asthenia, depression, decreased of concentration and sexual desire. Laboratoryevaluation revealed Ferritin level 2126 ug/L and transferrin saturation always more than 99%. Liver function tests also increasedsignificantly. Some of his family’s members have the same disease as he has. He was diagnosed as primary hemochromatosis and hadperformed phlebotomy routinely. After phlebotomy has done, he recovered based on clinical and laboratorial findings.